Spontaneous triplet pregnancy and trap sequence, case report - Engin Yıldırım (BMC, 2019)
Abstract Background Spontaneous multiple pregnancies are rare, and the incidence of spontaneous triplet pregnancy is about 1/4000. TRAP (Twin Reversed Arterial Perfusion) sequence has acardiac foetus with non-viable multiple anomalies, and there is a pump foetus which feeds this foetus with placental anastomoses. TRAP sequence phenomena is quite rare in triplet pregnancies. Case presentation The patient who applied to our clinic was 30 years old. Monochorionic diamniotic triplet pregnancy was detected by ultrasonographic examination. First amniotic sac had one foetus (Foetus A). Ultrasonographic evaluation of Foetus A revealed gestational age of 31 weeks, adequate amniotic fluid and no fetal structural anomalies. The second amniotic sac contained 2 foetuses and polyhydromnios. Ultrasonic measurements of Foetus B were consistent with 32 weeks gestational age. Color flow doppler indicated Foetus B was the pump foetus. Foetus C was an acardiac foetus with no sonographic visualization of cranium, thoracic organs or extremities, but abdominal circumference consistent with 28 weeks. Pregnancy was followed conservatively and evaluated regularly by ultrasonography twice a week. When prolonged bradycardia was detected in fetus B at 35 4/7 weeks, emergency cesarean section was performed. Two healthy fetuses weighing 2 kg were delivered each with an 8/10 APGAR score (Appearance, Pulse, Eye Insertion, Activity, Respiration). Conclusion This case was managed without any invasive procedures and demonstrates that treatment of TRAP sequence cases can be individualized considering clinical conditions, the size of the acardia twin and extent of placental venous anastomoses.